Examining the role of friendship quality in enhancing university students' learning motivation - Rupawan, Muhammad Rayhan Rajja Mujahidin; Febriani, Adelia Putri Semi (Empathy : Jurnal Fakultas Psikologi, 2024)
This study aims to examine the impact of the quality of the friendship environment on the learning motivation of students in several public universities in Indonesia. A qualitative research design with a case study approach was employed for this investigation. Data were collected through in-depth interviews with six students, selected using a purposive sampling technique. Thematic analysis was used to analyze the data. The findings indicate that a high-quality friendship environment characterized by emotional support, collaborative group work, and mutual reminders about assignments positively influences students' learning motivation. Increased motivation is evident in students' habits of completing assignments on time and their enthusiasm in attending lectures. Additional factors influencing learning motivation include self-encouragement, family support, and encouragement from peers. This study concludes that the quality of the friendship environment is a crucial factor in fostering students' academic success.